Price Level Convergence Among United States Cities: Lessons for the European Central Bank - Stephen Cecchetti; Nelson C. Mark; Robert Sonora (Oesterreichische Nationalbank (OeNB), 1998)
We study the dynamics of price indices for major U.S. cities. Using panel econometric methods, we find that relative price levels among cities mean revert, but at a surprisingly slow rate. In a panel of 15 cities from 1918 to 1995, we estimate the half life of convergence to be approximately 9 years. The following hypotheses are investigated as explanations for the slow convergence: (i) Arbitrage impediments induced by transportation costs, and (ii) and the inclusion of nontraded goods prices in the overall price index as suggested by the Balassa-Samuelson hypothesis. Our estimates provide an upper bound on convergence rates that participants in European Monetary Union may experience.
Keywords: 330; Purchasing power parity; Convergence; European Monetary Union